PENGARUH PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT BARATA INDONESIA TAHUN 2009-2011 - Irwanti, Novika; Rinaldi, Rinaldi; Eriswanto, Elan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This study aimed to determine the effect of the level of account receivable turnover on profitability in PT Barata Indonesia in 2009-2011. Variables used in this study is accounts receivable turnover, and profitability. This research method in this study is a quantitative method, a sample of 36 financial statements of PT Barata Indonesia for the years 2009-2011. For receivables turnover can be seen with the testing criteria that if tcount>ttable (5,372>2,028) then H0 is rejected Ha accepted. To see the significance , visible results ttable statistic at a significance level of 5% sig = 0,000 > 0,05 significance level 0,05 (5%). The result show that the influence turnover partially and simultaneously affect the profitability of PT Barata Indonesia (Persero).